Potential use of hybrid vermitea-chemical solution for cultivation of hydroponic vegetables - Abdullah, Nur Syahirah (2019)
At present, hydroponic cultivation use chemical nutrient solution to provide nutrients for plant growth. Ironically, crop production with less chemical application would significantly improve the nutritional level of the crop over the full-chemicals counterpart. Therefore, the present study formulate a hybrid solution (hybrid vermitea-chemical hydroponic solution) as an alternative to increase the crop growth performances and nutritional quality while reducing the chemical application in hydroponic cultivation. Vermitea is an organic extract of vermicompost that contains high levels of beneficial microbes and soluble nutrients. While, the hybrid vermitea-chemical solution is a combination of vermitea with a certain level of Cooper commercial chemical hydroponic solution. In this study, Chinese kale were grown in hybrid vermitea-chemical hydroponic solutions that include; VT25 (25% vermitea + 75% Cooper hydroponic solution), VT50 (50% vermitea + 50% Cooper hydroponic solution), VT75 (75% vermitea + 25% Cooper hydroponic solution) and VT100 (100% vermitea) with CP (‘Cooper’; commercial chemical hydroponic solution) as control. The nutrient contents of the hydroponic solutions were measured using Auto Analyzer for N and P and Atomic Absorption Spectrometry (AAS) for K, Mg, Ca, Fe, Zn, Mn and Cu. The vegetative growth performances (chlorophyll content, height, number of leaves, leaves area and fresh weight) and the vegetables quality (mineral contents, total phenolic content (TPC) and antioxidant activity) of the vegetables were also measured. The results showed that the reduce of chemical Cooper solution by 25% in VT25 solution recorded higher concentration of P, K, Mg, Fe, Zn, and Cu compared to the other hybrid treatments including the CP solution. The vegetative performances (chlorophyll content, height, number of leaves, leaves area and fresh weight) for Chinese kale in VT25 also recorded as good as its counterpart in CP solution. Meanwhile, the antioxidant activity of Chinese kale planted in hybrid vermitea-chemical solutions was significantly higher but, total phenolic contents recorded no significant different compared to vegetable in CP solution. The study suggested that the hybrid vermitea-chemical solution could be potentially used for hydroponics, thus the usage of chemical fertilizers in producing vegetables crops could be reduced.